The toxic effect of metal oxides on the animal organism - Шкромада, О. І. (Scientific Progress & Innovations, 2012)
Article is devoted to safety, and effectiveness of nanometal oxides: titanium dioxide. Red iron oxide pigment and copper sulfate. Toxicological studies have shown that metal oxides (Fe2О3 і ТiО2) exhibit their bactericidal activity in concentrations 0,2-2 mg/l. They have very low cytotoxicity, and lethality. Nanopowder is characterized by copper 60 % toxicity in the dose 50 mg/kg and the maximum expression of toxicity in the range 125- 500 mg/kg.